Potential Impact of Dietary Choices on Phosphorus Recycling and Global Phosphorus Footprints: The Case of the Average Australian City - Metson, Geneviève S.; Cordell, Dana; Ridoutt, Brad (Frontiers in Nutrition, 2016)
Changes in human diets, population increase, changes in farming practices, and globalized food chains have led to dramatic increases in the demand for phosphorus fertilizers. Long-term food security and water quality are however threatened by such increased phosphorus consumption because the world’s main source, phosphate rock, is an increasingly scarce resource. At the same time losses of phosphorus from farms and cities have caused widespread water pollution. As one of the major factors contributing to increased phosphorus demand, dietary choices can play a key role in changing our resource consumption pathway. Importantly, the effects of dietary choices on phosphorus management are two-fold: First, dietary choices affects a person or region’s ‘phosphorus footprint’ – the magnitude of mined phosphate required to meet food demand. Second, dietary choices affect the magnitude of phosphorus content in human excreta, and hence the recycling- and pollution-potential of phosphorus in sanitation systems. When considering options and impacts of interventions at the city scale (e.g. potential for recycling), dietary changes may be undervalued as a solution towards phosphorus sustainability. In an average Australian city for example, a vegetable-based diet could marginally increase phosphorus in human excreta (8% increase). However such a shift could simultaneously dramatically decrease the mined phosphate required to meet the city resident’s annual food demand by 72%. Taking a multi-scalar perspective is therefore key to fully exploring dietary choices as one of the tools for sustainable phosphorus management.